2015
DOI: 10.1098/rsos.150301
|View full text |Cite
|
Sign up to set email alerts
|

Omura’s whales (Balaenoptera omurai) off northwest Madagascar: ecology, behaviour and conservation needs

Abstract: The Omura’s whale (Balaenoptera omurai) was described as a new species in 2003 and then soon after as an ancient lineage basal to a Bryde’s/sei whale clade. Currently known only from whaling and stranding specimens primarily from the western Pacific and eastern Indian Oceans, there exist no confirmed field observations or ecological/behavioural data. Here we present, to our knowledge, the first genetically confirmed documentation of living Omura’s whales including descriptions of basic ecology and behaviour fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(94 citation statements)
references
References 38 publications
5
84
0
Order By: Relevance
“…As described by Cerchio et al (2015), this individual showed evidence of asymmetrical colouration of the lower jaws, with a darkly pigmented left jaw (Fig. 2 a) and lightly pigmented right jaw (Fig.…”
Section: Jaw Asymmetrysupporting
confidence: 66%
See 4 more Smart Citations
“…As described by Cerchio et al (2015), this individual showed evidence of asymmetrical colouration of the lower jaws, with a darkly pigmented left jaw (Fig. 2 a) and lightly pigmented right jaw (Fig.…”
Section: Jaw Asymmetrysupporting
confidence: 66%
“…4. Asymmetrical chevron on both right and left sides Lightly pigmented chevron anterior to the dorsal fin evident on both sides but more pronounced on right side of the body, displaying a double-banded pattern also described by Cerchio et al (2015).…”
Section: Presence Of a Prominent Single Medial Ridgementioning
confidence: 68%
See 3 more Smart Citations